Evaluating Patient Profile, Follow-Up Rates and Barriers to Follow-Up at a Student-Run, Community-Based Tuberculosis Testing Program - Foroushani, Sophia; Crawford, Andrew; Woodbridge, Alexandra; Frechtling, Dan; Ali, Juzar (Journal of Student-Run Clinics, 2022)
Background: The Tulane Student-Run Tuberculosis (TB) Program provides TB risk evaluation, skin testing (TST), and referrals at six homeless shelters and rehabilitation facilities. To date, there has been no evaluation of the programâ€™s patient profile. The objective of this study was to determine the symp-toms and risk factors for TB present in the program’s clients, calculate follow-up rates for TST reading, and determine factors associated with an increased rate of missing reading appointments. Methods: This retrospective chart review examines the prevalence of risk factors and TB symptoms, evaluates risk stratification, and determines barriers to follow-up for TST over a 33-month period. Rel-ative risks (RR) were calculated to determine the association between risk stratification, positive TST, and loss to follow-up. Z-values were calculated, and p-values were determined as the area of the dis-tribution outside of +/- z. P-values <0.05 were considered statistically significant. Results: Of 6,198 individuals seen, 479 were referred to higher care, 238 received 30-day clearances, 34 deferred testing, and four were sent to the hospital. Of 5,443 TSTs placed, 4,155 were read and 214 were positive. Individuals who had any risk factors were at significantly increased risk of not attending TST reading (RR 2.14, 95% Confidence interval [CI] 1.96-2.34, p<0.01) and, for those who did attend, of having a positive TST (RR 1.52, 95% CI 1.17-1.98, p<0.01). Higher risk of no-show and positive TST was also seen in homeless individuals (RR 3.44, 95% CI 2.92-4.07, p<0.01 and RR 2.10, 95% CI 1.52-2.90, p<0.01, re-spectively) and those with intermediate-risk stratification (RR 1.25, 95% CI 1.11-1.41, p<0.01 and RR 1.32, 95% CI 1.01-1.72, p=0.04, respectively). Conclusions: Individuals experiencing homelessness and those with intermittent TB risk stratification are at increased risk for positive TST. Both homelessness and the presence of any TB risk factors in-crease the risk of loss to follow-up.